KINERJA PEGAWAI APARATUR SIPIL NEGARA DALAM PELAYANAN ADMINISTRASI DI KABUPATEN TAKALAR - Sukri, Muh Zaad; Abdi, Abdi; Hawing, Hardianto (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2024)
The aim of the research is to determine the performance of State Civil Service Employees (ASN) in Administrative Services at the Mangarabombang District Office, Takalar Regency. "This type of research uses qualitative methods with descriptive research type, data collection techniques through observation, interviews and documentation. The results of the research show that Quality work, there is a clear improvement in the quality of work at the Mangarabombang District Office, which can be seen from the positive evaluations given by employees. The quantity, volume and efficiency of administrative services at the Mangarabombang District Office vary depending on the type of service and office capacity. On time punctuality, ASN employees in Mangarabombang District are generally disciplined in terms of the stipulated time for entering and leaving the office. Effectiveness, it can be seen that resources at the Mangarabombang District Office have increased with technological advances and larger budget allocations. Independence, ASN employees at the Mangarabombang District Office have demonstrated good service quality by acting independently, taking initiative.